About some obstacles to the integration of Central Asian states (Journal of Philosophy Culture and Political Science, 2019)
Abstract. The paper discusses the major issues and factors that create certain obstacles to the integration processes in Central Asian region that eventually become a barrier for successful integration of countries of the regiom. The issues include political, economic, hydro and social problems and processs affecting the integration among the Central Asian states (former Soviet republics). The authors of the articledraw attention to the fact that Central Asian countries are lacking the common system of economic management of the region. The article explores about the complicated cases in resolving territorial disputes in the region. It also mentions the aggrevated situation with the use of water resources between the states of Central Asia. The methodology implied in the research is mainly based on the use of comparativepolitics tools to discover the major differences between Kazakhstan Uzbekistan, Turkmenistan, Kyrgyzstan and Tajikistan to understand how it affects on entire integration processes between them.Key words: integration, Central Asian region, territorial disputes, political situation, borderline, illegal trade, terrorism.